Numerical simulation of a Deep Borehole Heat Exchanger in the Krafla geothermal system - Renaud, Théo; Verdin, Patrick G.; Falcone, Gioia (Elsevier, 2019)
The geothermal energy sector is facing numerous challenges related to heat recovery efficiency and economic feasibility. Research on superheated/supercritical geothermal systems is progressing in Europe, triggered by the Iceland Deep Drilling project (IDDP) and the DESCRAMBLE project in Italy. In Iceland, the IDDP-1 well, which reached a magma intrusion at a depth of 2100 m, raised new opportunities to untap the geothermal potential near magmatic intrusions. Given their highly corrosive nature, geothermal fluids weaken the wellbores integrity during conventional geothermal production. Closed-loop Deep Borehole Heat Exchangers (DBHE) that do not require fluid exchange between the subsurface and the wells represent a strategic alternative for recovering heat from these unconventional geothermal resources, while minimising the risk of in situ reservoir damage. The thermal influence and heat recovery associated with a hypothetical DBHE drilled into the IDDP geological settings are investigated via Computational Fluid Dynamics (CFD) techniques, simulating 30 years of production. Two wellbore designs are modelled, based on simplified geological properties from the IDDP-1 well description. The results show that, during the first year of production, the output temperature is function of the working fluid velocity before reaching pseudo-steady state conditions. The cooling perturbation near the bottom hole is shown to grow radially from 10 to 40 m between 1 and 10 years of production, and the calculated output power reaches up to 1.2 MWth for a single well. The heat transfer at the bottom well bore is enhanced by extending the inner well deeper into the ground. Subject to full economic analysis to be performed at field scale, the significantly lower technical risks of the closed-loop DBHE could outweigh the lower thermal output per well compared to theoretical expectations from open-loop Enhanced Geothermal Systems (EGS).
Keywords: Wellbore heat exchanger; Geothermal energy; Magma chamber; CFD